Controlling fatigue crack paths for crack surface marking and growth investigations (Fracture and Structural Integrity, 2015)
While it is well known that fatigue crack growth in metals that display confined slip, such as high strength aluminium alloys, develop crack paths that are responsive to the loading direction and the local microstructural orientation, it is less well known that such paths are also responsive to the loading history. In these materials, certain loading sequences can produce highly directional slip bands ahead of the crack tip and by adjusting the sequence of loads, distinct fracture surface features or progression marks, even at very small crack depths can result. Investigating the path a crack selects in fatigue testing when particular combinations of constant and variable amplitude load sequences are applied is providing insight into crack growth. Further, it is possible to design load sequences that allow very small amounts of crack growth to be measured, at very small crack sizes, well below the conventional crack growth threshold in the aluminium alloy discussed here. This paper reports on observations of the crack path phenomenon and a novel test loading method for measuring crack growth rates for very small crack depths in aluminium alloy 7050-T7451 (an important aircraft primary structural material). The aim of this work was to firstly generate short- crack constant amplitude growth data and secondly, through the careful manipulation of the applied loading, to achieve a greater understanding of the mechanisms of fatigue crack growth in the material being investigated. A particular focus of this work is the identification of the possible sources of crack growth retardation and closure in these small cracks. Interpreting these results suggests a possible mechanism for why small fatigue crack growth through this material under variable amplitude loading is faster than predicted from models based on constant amplitude data alone.
Keywords: Fatigue crack growth; Crack closure; Crack paths